HEYZINE FLIPBOOK IN ENGLISH LANGUAGE LEARNING: STUDENTS’ PERCEPTIONS - Siena, M. Haikal Ibnu; Manurung, Jenny Elvinna; Ria, Nita (English Community Journal, 2026)
This study investigated students’ perceptions and the benefits of using the Heyzine Flipbook as a digital learning medium among eleventh-grade students at SMA Negeri 11 Palembang in the 2025/2026 academic year. Employing a quantitative survey design, the study involved 165 students selected through cluster random sampling from a population of 392 students. Data were collected using a close-ended questionnaire based on a four-point Likert scale, covering two main aspects: students’ perceptions and perceived benefits. The instrument demonstrated high reliability with Cronbach’s alpha of 0.890. The findings revealed that 98.12% of students expressed positive perceptions toward the Heyzine Flipbook. The application enhanced students’ motivation, improved comprehension, and supported English language development, indicating its effectiveness as an engaging and accessible digital learning tool. It also promoted independent learning and increased students’ engagement through interactive and visually appealing features, contributing to a more effective classroom learning environment overall in diverse instructional contexts and settings.